Seronegative Visceral Varicella Zoster Infection â A Not So Benign Skin Infection - Tumma, Abishek; Shah, Darshan; Seo, Shiney (Journal of Medical Biomedical and Applied Sciences, 2018)
Varicella zoster virus (VZV) infection is usually a self-limiting cutaneous childhood disease typically occurring due to impaired cell-mediated immunity. One manifestation of VZV is a visceral infection accounting for less than 15% of all VZV infections. We describe a severe case of visceral varicella infection several months following an autologous stem cell transplant for a high-grade B-cell lymphoma. The patient initially presented with abdominal pain accompanied by severe hepatitis which preceded the cutaneous manifestation. Initial serological testing was negative due to significant hypo gamma globulinemia following previous chemotherapy. However, the diagnosis was confirmed on VZV DNA PCR analysis of the vesicles. The patient developed further visceral complications including encephalopathy, gastritis, hiccups, colonic pseudo-obstruction, normocytic anaemia and thrombocytopenia. The infection responded well to intravenous acyclovir and intravenous immunoglobulin therapy. This is the first reported case report of seronegative VZV infection with an extensive visceral involvement likely caused by the underlying immunoglobulin deficiencies.